Economic Obstacles to Education in Ireland. (7th May 2021) - Doyle, David M; Muldoon, Marie; Thompson, Stephanie; Murphy, Muiread
Abstract: This policy note highlights the costs of sending a child to school in Ireland and explores the extent to which these represent a significant economic barrier to schooling for low-income families. It also evaluates the efforts to reduce early school leaving and examines the increasing commodification of education in Ireland.